Laboratory and greenhouse experiments were carried out during April-October 1996 to investigate the response of three soybean varieties to the combined infestation ofMeloidogyne incognita (Kofoid & White) Chitwood and three root-gall nematode colonizing fungi (MCF). The experiments were done in a factorial completely randomized design with three replications. Treatments in laboratory test were combination of three soybean varieties, i.e. Black soybean (VI)' Wilis (V z) and Lokon (V,J, t - A. Muin Adnan; R. Suseno; S. Tjitrosoma; S. Radi; S. Wardojo; A. Rambe (Buletin Hama dan Penyakit Tumbuhan, 1998)
Laboratory and greenhouse experiments were carried out during April-October 1996 to investigate the response of three soybean varieties to the combined infestation ofMeloidogyne incognita (Kofoid & White) Chitwood and three root-gall nematode colonizing fungi (MCF). The experiments were done in a factorial completely randomized design with three replications. Treatments in laboratory test were combination of three soybean varieties, i.e. Black soybean (VI)' Wilis (V z) and Lokon (V,J, two initial population densities of M. incognita, i.e. 0 and 300/200 ml growth medium, and three MCF species, i.e. Paecilomyces sp., Gliocladium catenulatum, and Trichoderma viride. The greenhouse treatments were the combination of three soybean varieties (Vb V2, V3), three initial population densities ofM. incognita (0, 1000, and 2000/4 I growth medium), and three MCF species. Result of laboratory tests showed that the combination ofM. incognita and three MCF species significantly reduced the damage levelofM. incognita and root weight loss. Reduction of shoot weight loss occurred only in slightly resistant and susceptible varieties in combination with PaeciIomyces sp. and G. catenulatum. Combination ofT. viride and M. incognita on three soybean varieties showed synergistic interaction. Result of greenhouse tests showed that all of the MCF isolates significantly reduced the damage level and the final population ofM. incognita. However, only Paecilomyces sp. could reduce the root weight loss, relative plant growth rate, and harvested seeds. These reducing effects were achieved on Lokon variety only, that is susceptible to M. incognita. There was no synergistic interaction between M. incognita and T. viride in the greenhouse test, even though the root colonization frequency of Trichoderma sp. on the susceptible variety was rather high.